Amplified Waveguide Teleconnections Along the Polar Front Jet Favor Summer Temperature Extremes Over Northern Eurasia. Issue 13 (8th July 2021) - Xu, Peiqiang; Wang, Lin; Vallis, Geoffrey K.; Geen, Ruth; Screen, James A.; Wu, Peili; Ding, Shuoyi; Huang, Ping; Chen, Wen
Abstract: An apparent increase in the frequency of summer temperature extremes over northern Eurasia has been observed in the past decade. Some of these high‐impact events were associated with amplified waveguide teleconnections embedded in the polar front jet, but it remains unclear if extreme temperatures are robustly and routinely related to amplified waves along the polar front jet. This study systematically examines relationships between planetary wave activity and temperature extremes using observations, reanalysis, and large‐ensemble simulations from multiple climate models. Months with extreme temperatures over northern Eurasia generally have amplified wave activity along the polar front jet, whereas months with near‐average temperatures tend to have attenuated wave activity. Waveguide teleconnections are particularly amplified during extremely hot and cold summer months over eastern Europe and western Russia. These findings demonstrate the important role of waveguide teleconnections along the polar front jet in generating regional temperature extremes over northern Eurasia. Plain Language Summary: Atmospheric circulation anomalies move horizontally across Earth. At a particular location, this can be seen in the passage of low‐ and high‐pressure systems over time, much like the peaks and troughs of an ocean wave. Sometimes these atmospheric waves can become trapped, preventing their northward or southward migration, and are guided predominantly west to east along a common path, and when they do this, they often grow in amplitude. Amplified atmospheric waves may be a cause of prolonged heatwaves, such as those that occurred in eastern Europe and western Russia in summer 2010 and that resulted in 55, 000 deaths and economic losses of more than 15 billion. This study examines the relationship between wave activity and summer temperature extremes over northern Eurasia. We find that wave activity tended to be greater than normal during those summer months that had extreme temperatures. In contrast, wave activity was commonly less during months with near‐average temperatures. In particular, waves were especially amplified during extremely hot and cold summer months over eastern Europe and western Russia. This work helps to understand the causes of extreme heat waves over northern Eurasia in order that society may be better prepared when they occur. Key Points: Summer temperature extremes over northern Eurasia are linked with amplified waveguide teleconnections embedded in the polar front jet The above relationship is robust in both observations and large‐ensemble simulations with multiple climate models The relation is particularly strong for hot and cold events over eastern Europe and western Russia